Combined Evaluation of MAP1LC3B and SQSTM1 for Biological and Clinical Significance in Ductal Carcinoma of Breast Cancer - Pei-Feng Liu; Chih-Wen Shu; Hsiu-Chen Yang; Cheng-Hsin Lee; Huei-Han Liou; Luo-Ping Ger; Yen-Dun Tony Tzeng; Wen-Ching Wang (Biomedicines, 2021)
Breast cancer is the leading cause of cancer death in women worldwide. The microtubule-associated protein light chain 3B (MAP1LC3B) and adaptor sequestosome 1 (SQSTM1) are two major markers for autophagy. Increased protein levels of MAP1LC3B and SQSTM1 are considered to be causes of autophagy inhibition or activation in various types of cancers. However, the roles of MAP1LC3B and SQSTM1 in breast cancer are still not clear. Using a tissue microarray from 274 breast invasive ductal carcinoma (IDC) patients, we found that tumor tissues showed higher protein levels of MAP1LC3B and cytoplasmic SQSTM1 in comparison to those in adjacent normal tissues. Moreover, high levels of MAP1LC3B were associated with better survival, including disease-specific survival and disease-free survival (DFS) in IDC patients. Furthermore, high co-expression of MAP1LC3B and SQSTM1 was significantly associated with better DFS in IDC patients. Astonishingly, the autophagy inhibitor accumulated the protein levels of MAP1LC3B/SQSTM1 and enhanced the cytotoxic effects of cisplatin and paclitaxel in MCF7 and BT474 breast cancer cell lines, implying that autophagy inhibition might result in poor prognosis and chemosensitivity in IDC. Taken together, high co-expression of MAP1LC3B and SQSTM1 might serve as a potential diagnostic and prognostic biomarker for IDC patients.